1992
DOI: 10.1016/0885-3924(92)90049-n
|View full text |Cite
|
Sign up to set email alerts
|

System functionality and physicochemical model of fentanyl transdermal system

Abstract: Fentanyl is an opioid traditionally administered by infusion or injection and more recently in a rate-controlled transdermal dosage form. This system is a four-layer laminate on a protective liner. A backing layer seals and protects the drug reservoir, the source for continuous delivery of fentanyl. A membrane controls the release rate of fentanyl from the system. An adhesive layer attaches the system to skin and releases an initial loading dose of fentanyl. The rate of fentanyl delivery through skin is determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 4 publications
0
60
0
Order By: Relevance
“…al. have reported that the application of the transdermal fentanyl patch to the broken skin can increase blood fentanyl concentrations by 5 times [15]. A similar case [6] included a 6-year-old, 27-kg girl admitted to the hospital in the morning due to the altered mental status after her grandfather applied the Durogesic 25 μg/h transdermal patch over abrasion on her back the evening before.…”
Section: Discussionmentioning
confidence: 99%
“…al. have reported that the application of the transdermal fentanyl patch to the broken skin can increase blood fentanyl concentrations by 5 times [15]. A similar case [6] included a 6-year-old, 27-kg girl admitted to the hospital in the morning due to the altered mental status after her grandfather applied the Durogesic 25 μg/h transdermal patch over abrasion on her back the evening before.…”
Section: Discussionmentioning
confidence: 99%
“…9 Fentanyl is absorbed through a rate-limiting membrane by a process of passive cutaneous diffusion when administered by the transdermal route. 10 The drug forms a depot within the skin before entering the microcirculation and, as a result, exhibits delayed pharmacokinetic properties. 1-2 Therapeutic fentanyl blood levels are reached approximately 12-16 hours after the initial application of transdermal fentanyl patches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, variations in skin thickness and degree of keratinization will alter its systemic bioavailability and account for much of the great interindividual variability observed with transdermal fentanyl absorption [41][42][43]. This can be seen in Figure 2, in which there is a wide range around the mean serum fentanyl concentration in transdermal fentanyl users.…”
Section: Clinical Pharmacology Of Transdermal Fentanyl Patchesmentioning
confidence: 99%
“…Skin surface areas with similar stratum corneum thickness typically possess similar diffusion rates within an individual, explaining why the chest, extremities, and abdomen are acceptable sites for transdermal device application without the need for any dosage changes [41,44]. Following application of a transdermal fentanyl device to broken skin, blood fentanyl concentrations can rise 5-fold [42]. Exposed tissue lacking a stratum corneum, such as mucosa, has a >30-fold increase in fentanyl absorption, and more predictable pharmacokinetics [45].…”
Section: Clinical Pharmacology Of Transdermal Fentanyl Patchesmentioning
confidence: 99%
See 1 more Smart Citation